Feeding and Feeding habits of three main fish species in Lake Baringo, Kenya - Musyoka, Brayant; Bochabery O; Amobi, Ajwang (Advances in Aquaculture and Fisheries Management, 2013)
The diets of three fish species of commercial importance in Lake Baringo, Protopterus aethiopicus, Clarias gariepinus and Oreochromis niloticus, were determined using frequency of occurrence and volumetric methods between April 2008 and March 2010. Seine and gill nets were used to catch a total of 430 fish specimens. The diet of P. aethiopicus was 94.3% molluscs with a frequency of occurrence of 98.6% of stomachs with food. Adult C. gariepinus fed mainly on fish with 75% of the stomachs with food containing fish remains and mean of 49.2% contribution by volume. C. gariepinus also fed on zooplankton, especially the cladoceran Daphnia barbata. The food items in the stomachs of O. niloticus consisted mainly of algae, detritus and zooplankton. Algae was consumed by O. niloticus of all length classes in proportions ranging from 26.5 to 88.1%. The importance of zooplankton as food for O. niloticus decreased with size of fish. The study reveals the importance of zooplankton as food for O. niloticus and C. gariepinus in Lake Baringo. There is need to rehabilitate the catchment of Lake Baringo so as to improve the water quality thus improve productivity.